The decline of intellectualism in higher Islamic traditional studies: reforming the curriculum - Hashim, Rosnani (IIUM Press, 2015)
The issue of the waning of intellectualism in higher Islamic Traditional Sciences is the subject of Chapter 6. The fact is the number of faculties and universities offering Islamic traditional sciences or studies has slowly increased over the past decades. But the Islamic community has not felt their graduates’ impact other than as teachers or religious personnel. In fact, if the criteria used to assess Islamic education is the growth of a genuine, original, and adequate Islamic thought or intellectualism, then most of these institutions have failed to provide such an education. The author examines the goals and curriculum of higher Islamic education and the conditions conducive for the growth of intellectualism. She argues that poor pedagogy, which does not offer teaching methods that encourage critical and ethical thinking, contributed to the state of affairs. Further, she argues that the basic problem is the inadequate conceptualization of knowledge as regards Islamic epistemology in the curriculum and the lack of academic freedom. She asserts that the issue of what knowledge is most valuable for today’s intellectual and ethical Muslims has not been resolved and that this affects the curriculum structure and, inevitably, the programs of Islamic traditional sciences..